Tannins of tamarind seed husk: Preparation, structural characterization, and antioxidant activities - Sinchaiyakit P. (2017)
The high content (about 39%) of polymeric tannins in tamarind (Tamarindus indica L.) seed husk (TSH) was demonstrated, and an extract (crude TSE) with a high content (about 94%) of polymeric tannins was prepared from TSH with a one pot extraction using ethanol/water (3:2, v/v). The crude TSE was further purified with Sephadex LH20 to give one fraction (metTSE) eluted with methanol/water (3:2, v/v) and another (acTSE) eluted with acetone/water (3:2, v/v). The tannins of acTSE were established as polymeric proanthocyanidins (PA) by 13 C NMR spectroscopy; this was further confirmed by IR and UV spectroscopy, n-BuOH/HCl and vanillin assays, and from HPLC pattern. The ratio of procyanidins to prodelphinidins was 2:3, and the average degree of polymerization of acTSE was 7. Galloylated flavan-3-ols were not detected in acTSE. The main ingredients of metTSE were confirmed to be polymeric PA by 13 C NMR spectroscopy. The antioxidant activities using DPPH and ABTS assays were investigated. The IC 50 values of acTSE were 4.2±0.2 (DPPH assay) and 6.2±0.3 μg/mL (ABTS assay).